Research progress on the mechanism of the Hedgehog signaling pathway during mandibular development - XU Yao, LI Wenjin (口腔疾病防治, 2024)
The source and process of mandible development are significantly different from those of other bones in the body, and abnormal development can lead to various bone-related diseases, seriously affecting the quality of life of patients. In recent years, the role of the Hedgehog signaling pathway in bone development has received increasing attention. The Hedgehog gene includes three subtypes: Sonic Hedgehog (Shh), Indian Hedgehog (Ihh), and Desert Hedgehog (Dhh). Shh and Ihh can participate in bone metabolism regulation through various pathways, with Shh primarily involved in limb development and Ihh playing a key role in endochondral osteogenesis. The Hedgehog signaling pathway includes Hedgehog signaling protein ligands, Patched (Ptch) receptors, Smoothed (Smo) receptors, nuclear transcription factors, glioma-associated oncogene homologues (Gli), and downstream target genes. The activation of typical Hedgehog signaling pathways requires the involvement of Gli, whereas atypical Hedgehog signaling is mainly regulated by Ptch, Smo, and others. Shh regulates various biological behaviors during early vertebrate embryogenesis, such as organ differentiation, neural stem formation, stem cell differentiation and proliferation, limb bone development, and tooth germ development. During the process of bone cell differentiation, Shh, Ptch1, and Gli1 are expressed in osteoblasts, further promoting the differentiation of bone marrow mesenchymal stem cells into osteoblasts and chondrocytes. IHh plays an indispensable functional role in bone growth, development, and homeostasis and participates in the formation of intramembrane bone collars, proliferation, and maturation of chondrocytes. IHh is expressed in mature skull osteoblasts and can act as a promoter of bone factor regulation of Ptch and bone morphogenetic protein (BMP) expression to induce intramembrane ossification. Brain and muscle ARNT-like protein 1 (BMAL1) can regulate the Hedgehog signaling pathway by binding to Ptch1 and Ihh, playing a crucial role in cartilage formation and endochondral osteogenesis in the temporomandibular joint. Hedgehog signal activators can improve the reduction in mandibular bone mass caused by BMAL1 deficiency. Hedgehog signaling imbalance can have a significant impact on bone development and lead to a series of bone diseases, such as abnormal bone development, fractures, osteoporosis, and osteoarthritis. The mechanism of the Hedgehog signaling pathway in relation to mandibular diseases has not been fully elucidated, and future research should seek to further explore Hedgehog signaling as a potential target for treating mandibular developmental-related diseases.